A bird's eye view on the role of dendritic cells in SARS‐CoV‐2 infection: Perspectives for immune‐based vaccines. Issue 1 (24th July 2021) - Galati, Domenico; Zanotta, Serena; Capitelli, Ludovica; Bocchino, Marialuisa
Abstract: Coronavirus disease‐19 (COVID‐19) is a complex disorder caused by the pandemic diffusion of a novel coronavirus named SARS‐CoV‐2. Clinical manifestations vary from silent infection to severe pneumonia, disseminated thrombosis, multi‐organ failure, and death. COVID‐19 pathogenesis is still not fully elucidated, while increasing evidence suggests that disease phenotypes are strongly related to the virus‐induced immune system's dysregulation. Indeed, when the virus‐host cross talk is out of control, the occurrence of an aberrant systemic inflammatory reaction, named "cytokine storm, " leads to a detrimental impairment of the adaptive immune response. Dendritic cells (DCs) are the most potent antigen‐presenting cells able to support innate immune and promote adaptive responses. Besides, DCs play a key role in the anti‐viral defense. The aim of this review is to focus on DC involvement in SARS‐CoV‐2 infection to better understand pathogenesis and clinical behavior of COVID‐19 and explore potential implications for immune‐based therapy strategies.